Nieuwe spirituelen: wel netwerken, maar steeds minder religie - Jespers, Frans (Religie & Samenleving, 2013)
An analysis of the numerous contemporary, ‘new’ spiritual practices in the Netherlands through the approach of comparative religion and anthropology of religion reveals several categories from very religious up to quite secular ones. The religious-like groups have church-like organizations, the secular ones look more like commercial enterprises. In both contexts spirituality means striving for a kind of psychological fulfillment in relation to an ultimate reality, often with the help of religious means. More scientific research is needed in order to distinguish adequately positive, liberating forms of new spirituality from harmful ones.